Heuristic algorithms for joint optimization of unicast and anycast traffic in elastic optical network-based large-scale computing systems - Markowski, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
In recent years elastic optical networks have been perceived as a prospective choice for future optical networks due to better adjustment and utilization of optical resources than is the case with traditional wavelength division multiplexing networks. In the paper we investigate the elastic architecture as the communication network for distributed data centers.
Keywords: elastic optical networks; optimization; distributed data center; algorithm; tabu search